Risk factors for disease severity among children with Covid-19: a clinical prediction model - David Chun‑Ern Ng; Liew, Chuin‑Hen; Tan, Kah Kee; Ling Chin; Grace Sieng Sing Ting; Nur Fadzreena Fadzilah; Lim, Hui Yi; Nur Emylia Zailanalhuddin; Shir Fong Tan; Muhamad Akmal Afan; Fatin Farihah Wan Ahmad Nasir; Thayasheri Subramaniam; et al. (Springer Nature, 2023)
Background: Children account for a significant proportion of COVID-19 hospitalizations, but data on the predictors of disease severity in children are limited. We aimed to identify risk factors associated with moderate/severe COVID-19 and develop a nomogram for predicting children with moderate/severe COVID-19.